Exploratory factor analysis-instrument for self-assessment of computation thinking skills and collaboration skills - Hery Sawiji; Wiedy Murtini; Nur Rahmi Akbarini; Sigit Permansah; Dede Rusmana (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study focuses on developing and validating instruments to assess the computational thinking skills (CTS) and collaboration skills (CS) of undergraduate students in Indonesia. Employing a quantitative research approach with the exploratory factor analysis (EFA) technique, the research process unfolded in three validation steps. First, face validity was established through expert judgment. Second, discriminant validity was examined using product-moment correlations and Cronbach’s alpha. Finally, EFA were employed to assess the factorial structure. The instrument development process followed five phases: drafting the instrument, face validity assessment by experts, data collection involving 242 undergraduate students as samples, discriminant validity analysis (product moment and Cronbach’s alpha), and EFA analysis to group items and construct dimensions. This study identified six dimensions for CTS (algorithmic thinking, cooperative thinking, problem reformulation, creativity, critical thinking, and systematic testing) and three dimensions for CS (knowledge sharing, planning, and responsibility). These findings support validating the CTS and CS self-assessment scale, making it a valuable tool for evaluating undergraduate student learning and researching computational thinking and CS in Indonesia. Researchers and educators are encouraged to utilize the CTS and CS instrument for self-assessment purposes and further exploration of these competencies among undergraduate students.